The Role of Democratization and Economic Freedom on Corruption: A Case study of ASEAN - Muhammad Hasyim Ibnu Abbas; Januar Kustiandi; Amin Syaifudin; Achmad Nurdiono (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study aims to determine the interaction effect of democracy and economic freedom on corruption in ASEAN, 2012-2021. The tool analysis used in this study is typology analysis to determine the position of each ASEAN country based on the level of Corruption, democracy, and economic freedom, and it was amplified by panel data regression with a fixed effect. Typology analysis shows that the higher the level of democracy and economic freedom, the better the Corruption Perception Index (CPI). Regression analysis also shows that when a country possesses economic freedom level below 6.25, then democracy has a negative effect on corruption. Likewise, when the level of democracy of a country is below 4.4 then a change of economic freedom will reduce the CPI instead. This corresponds to the typology analysis in which Malaysia and Singapore have levels of democracy and economic freedom over 4.4 and 6.25”on average”during 2012-2021.